Mutation screening and analysis of the APC gene in Malaysian FAP patients / Fiqri Dizar Khaidizar - Khaidizar, Fiqri Dizar (2012)
Mutations in the APC tumour suppressor gene cause Familial Adenomatous Polyposis (FAP), a predisposition to colorectal cancer. This condition is characterized by adenomatous polyp formation in the colon and rectum which may advance to malignancy if not detected and treated early. FAP is 100% penetrant and segregates in an autosomal dominant manner. Screening for mutation in the APC gene is part of the preemptive genetic screening and risk assessment efforts for individuals with high risk of FAP. Knowledge of mutation spectrum that is prevalent in a certain population is essential to ensure precise prognosis of FAP by genetic testing. As such, this study was done to screen for pathogenic APC mutations in a set of Malaysian FAP patients and to reveal more information on the local APC mutation spectrum. DNA from each patient’s blood sample were purified and subjected to PCR-SSCP analysis. Each exon of the APC gene was amplified by PCR using exon-specific primers. PCR-amplified products were then denatured and separated on MDE gel for approximately 16 hours. The gel was later stained by silver staining. Samples with distinct band mobility shift were sent for DNA sequencing to determine the nature of the sequence variation. Three truncating mutations and a single nucleotide polymorphism (SNP) were detected from the screening. Two of the mutations detected (c.847C>T and c.1690C>T) are point mutations that created premature stop codons while another mutation (c.875-876insT) is a frameshift mutation. c.847C>T and c.1690C>T mutations have been reported extensively in many cohorts while mutation c.875-876insT is believed to be novel. The SNP detected in this study (c.1635G>A), on the other hand, has been reported in SNP databases. c.847C>T, c.1690C>T and c.875-876insT are expected to cause truncation of the APC protein, which is consistent with other previously reported APC gene mutations. Truncated APC protein can only weakly maintain cytoplasmic β-catenin concentration at the baseline level. This condition promotes hyperactivation in the transcription of Wnt target genes en route to colorectal carcinogenesis. The novel mutation detected here has expanded the knowledge of the APC mutations in the multiracial population of Malaysia. This would further assist in the establishment of a local APC mutation database that would benefit genetic testing and risk assessment strategies of FAP in the future. A splicing assay using a minigene expression system was also carried out to investigate the effect of c.847C>T (p.R283X) mutation on exon splicing in vitro since the mutation was found to reside in an exonic splicing enhancer (ESE) motif. A minigene carrying the mutation was constructed using splicing by overlap extension–PCR (SOE-PCR) technique and cloned into a mammalian expression vector. The vector was then transfected into HepG2 cultured cells. mRNA was later extracted from the cells 48 hours after incubation and subjected to reverse transcription PCR (RT-PCR) for analysis. The mutation was expected to cause skipping of exon 8 from the mature minigene transcript. cDNA analysis showed that the expected transcript sans exon 8 was absent. Instead, five transcripts of variable length were observed. Sequencing of these variants revealed that they were the minigene’s mRNA products of variable degree of splicing. The absence of the expected splicing product was thought to be due to the strength of the intron 7-exon 8 junction to define the boundary without necessitating the function of the adjacent ESE motif during splicing of exon 8, hence preserving exon 8 in the mature transcript.